En bogtrykker og boghandler i København. Claude Philiberts forbindelse med Societé typographique de Neuchatel 1771-1783 - Horstbøll, Henrik (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2012)
In 1755 Claude Philibert came from Geneva to Copenhagen, where he established himself as a bookseller. Until the 28th of April 1775 he was also a partner in a publishing bookshop and printer’s business in Geneva, which was run by Barthélemy Chirol. On the 3rd of August 1771 Claude Philibert contacted the Societé typographique de Neuchatel (STN) and his first order of books from Neuchatel was placed on the 17th of March 1772. J.F. Struensee had introduced unrestricted press freedom in September 1770, and pre-censorship was not reintroduced after Struensee’s fall from power in 1772. Until his business closed in 1783, Philibert imported 1,771 works from STN to Copenhagen. The French Enlightenment philosophers were richly represented: D’Holbach’s radical atheistic work, “Système de la Nature”, – and the debate it aroused – was amongst the first books sent from the STN to Copenhagen, and contemporary works by Voltaire, Rousseau, Helvetius and de la Mettrie followed. The bulk of the works however consisted of French novels and plays, and Louis-Sébastian Mercier’s futuristic novel “l’An 2440” was a bestseller, with 105 orders. The books were carried by barges from Neuchatel and Yverdon in Switzerland to Amsterdam, from where STN’s agents Panchaud & Houlez sent them on to Copenhagen. The books were normally unbound, but fastened together in blue paper. STN engaged in barter with Philibert & Chirol in Geneva, while for the trade with Copenhagen cash was preferred, businessman Frederik de Coninck serving as middleman. Philibert sold only a few copies of STN’s quarto edition of “l’Encyclopedie” (1777–80) because, as Philibert stated in his letters, the octavo edition from Lausanne & Bern (1778–82) dominated the Danish market due to its lower price. The import of another of STN’s large reprints: “Description des Arts et Métiers” (1771–83) was taken over in commission by the professor of history Johan Heinrich Schlegel, who became head of the Danish Royal Library in 1778. In 1779 Schlegel contrived STN’s dedication of vol. 9 of “Description des Arts et Métiers” to the King of Denmark – but without the prior permission of the royal family. As a book printer Claude Philibert himself participated in the market for the reprinting of censured French works. Letters reveal that in 1773 he printed “les Lettres de Ma. de Pompadour avec les Reponses” in 3 parts, octavo format; and his largest reprint in Copenhagen during during this period was Raynal’s “Histoire philosophique et politique”, Nouv. Éd., suivant la Copie a Amsterdam (1–7 in 6 volumes) 1773–74. The Societé typographique de Neuchatel was beyond doubt only one of many Claude Philibert’s connections, but the complete collection of letters sheds light on Philibert as bookseller and book printer during the last decade of his career in Copenhagen. This arbitrary glimpse provides documentation that Philibert was part of a European network, where book production and book trading were to a greater extent determined by language culture, language borders and conditions of censorship than dictated by state boundaries.